ANALISIS PERILAKU BIROKRASI DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KELURAHAN LAMBARA KECAMATAN TAWAELI - Sartika, Dewi (Katalogis, 2013)
This research was aimed at knowing and analyzing bureaucracy behaviors in running public service in Lambara, Tawaeli. Theories dealing with the bureaucracy behaviors comprising both individual and bureaucracy characteristic were taken from Miftah Thoha. This was qualitative. The research informants were selected by using a purposive sampling technique amd there were five informants determined. They were village chief. Cillage secretary, head of law and order section, and society. Next, the methods of gathering data were observation deep interview, and documents, while the tecnigue of data analysis comprised data reduction, data presentation, and verification. Based on the analisys, the research result showed that the the bureaucracy behaviors in running public service ini Lambara, Tawaeli have not shown his/her good characteristic. For example, the staff still have not had good ability, needs, and experience even thought they had good confidence and expectation. In addition, the bureaucracy characteristics have not shown maximum result in as much as the aspect aspects like hierarchy, duties, authority and responsibility still have not run well yet as expected. Only reward system and control system aspect have shown good result.